Будинок полкової канцелярії в Чернігові у 60-х роках ХІХ ст. - Доценко, А. (Сiверянський лiтопис, 2016)
У даній статті на документальних матеріалах Державного архіву Чернігівської області висвітлюється історія і ремонти будинку полкової канцелярії у першій половині 60-х років ХІХ ст. Данная статья посвящена истории и ремонтам дома полковой канцелярии в первой половине 60-х годов ХІХ века. In this article elucidates the history and building repairs of the regimental chancellery in the first half of the 60-s of XIXth century. The 60s in the building department of the Russian Empire affected of reorganization: the first half of the 60s (until 1865), when provincial building and road commissions still engaged of repairing of state-owned facilities, and the second half of the 60s (from 1865), when commissions, according to the decree of the Governing Senate were eliminated, and their functions, according to the same decree, were delegated to building departments that were found by provincial administrations.